Effects of iron deficiency and iron supplementation at the host-microbiota interface: Could a piglet model unravel complexities of the underlying mechanisms? - Abbas, Munawar; Hayirli, Zeynep; Drakesmith, Hal; Andrews, Simon C.; Lewis, Marie C. (Frontiers in Nutrition, 2022)
Iron deficiency is the most prevalent human micronutrient deficiency, disrupting the physiological development of millions of infants and children. Oral iron supplementation is used to address iron-deficiency anaemia and reduce associated stunting but can promote infection risk since restriction of iron availability serves as an innate immune mechanism against invading pathogens. Raised iron availability is associated with an increase in enteric pathogens, especially Enterobacteriaceae species, accompanied by reductions in beneficial bacteria such as Bifidobacteria and Lactobacillaceae and may skew the pattern of gut microbiota development. Since the gut microbiota is the primary driver of immune development, deviations from normal patterns of bacterial succession in early life can have long-term implications for immune functionality. There is a paucity of knowledge regarding how both iron deficiency and luminal iron availability affect gut microbiota development, or the subsequent impact on immunity, which are likely to be contributors to the increased risk of infection. Piglets are naturally iron deficient. This is largely due to their low iron endowments at birth (primarily due to large litter sizes), and their rapid growth combined with the low iron levels in sow milk. Thus, piglets consistently become iron deficient within days of birth which rapidly progresses to anaemia in the absence of iron supplementation. Moreover, like humans, pigs are omnivorous and share many characteristics of human gut physiology, microbiota and immunity. In addition, their precocial nature permits early maternal separation, individual housing, and tight control of nutritional intake. Here, we highlight the advantages of piglets as valuable and highly relevant models for human infants in promoting understanding of how early iron status impacts physiological development. We also indicate how piglets offer potential to unravel the complexities of microbiota-immune responses during iron deficiency and in response to iron supplementation, and the link between these and increased risk of infectious disease.